Kebijakan Terhadap Anak Berhadapan Hukum - Nur Arifah; Muhtar Said (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Children are a trust and a gift from God Almighty, because within them are already embedded the rights and dignity as complete human beings. In Law Number 11 of 2012 concerning the Juvenile Justice System in conjunction with Law Number 3 of 1977 concerning the Juvenile Court, the term